A rare case report: pregnancy with pancytopenia - Rajput, Yogesh; N. Wankhede, Uma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Pancytopenia is reduction in all the three major cellular elements of blood, hence it is the simultaneous presence of anaemia, leukopenia and thrombocytopenia. Here we present a case of a 28-year-old female, G4P3L1D2 with previous LSCS with 30 weeks gestation with pancytopenia managed with steroids and transfusions.